Chemical biology : selected papers of H. Gobind Khorana (with introductions) - Khorana, Har Gobind, 1922-2011 (World Scientific series in 20th century biology ;, 2000)
The first two chapters of this invaluable book trace the developments of the chemistry and macromolecular structures, respectively, of proteins and nuclei acids. Similarly, the introductions to the succeeding chapters review, step by step, the historical landmarks in the topics covered. These include discoveries of biological phosphate esters, nucleotides and nucleotide coenzymes (important in intermediary metabolism), the nature of the genetic material and biological synthesis of proteins, formulation of the problem of the genetic code, and perspectives on bioenergetics. The selected papers il.